2021
DOI: 10.1097/nmd.0000000000001364
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Anxiety, Depression, and Irritability Symptoms in Children During the COVID-19 Outbreak and Potential Risk Factors Associated With These Symptoms

Abstract: The aim of this study was to determine the frequency of anxiety, depression, and irritability symptoms in children during the COVID-19 outbreak and to investigate the associated factors of these symptoms. This study was conducted with 1071 children aged 6 to 17. Results showed that 49.9% of the participants had anxiety symptoms, 29.5% had depression symptoms, and 51.4% had irritability symptoms. Low age was a potential risk factor for anxiety symptoms. Female sex was a potential risk factor for anxiety and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
2
9
1
2
Order By: Relevance
“…This leads us to a particularly noteworthy result from this study: mental health and the HRQoL of Tyrolean children were not shown to be significantly impacted by actual exposure, while subjective threat experience proved to be the best predictor of children’s mental health and HRQoL (medium effect for posttraumatic stress symptoms, small effects for all other outcomes). Although some studies on children’s mental health during the COVID-19 pandemic identified exposure as a risk factor ( Dönmez and Uçur, 2021 ; Luijten et al, 2021 ), this finding is not so clear-cut, and our study found pandemic exposure to have no impact on children’s mental health. This could be because only a small percentage of participating families were exposed to the most traumatic aspects of the pandemic (e.g., death of a close relative or hospitalisation due to COVID-19).…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…This leads us to a particularly noteworthy result from this study: mental health and the HRQoL of Tyrolean children were not shown to be significantly impacted by actual exposure, while subjective threat experience proved to be the best predictor of children’s mental health and HRQoL (medium effect for posttraumatic stress symptoms, small effects for all other outcomes). Although some studies on children’s mental health during the COVID-19 pandemic identified exposure as a risk factor ( Dönmez and Uçur, 2021 ; Luijten et al, 2021 ), this finding is not so clear-cut, and our study found pandemic exposure to have no impact on children’s mental health. This could be because only a small percentage of participating families were exposed to the most traumatic aspects of the pandemic (e.g., death of a close relative or hospitalisation due to COVID-19).…”
Section: Discussioncontrasting
confidence: 90%
“…Research on previous disasters has shown that the severity of exposure to the disaster is strongly associated with the manifestation of mental health problems in children and that the development of posttraumatic stress symptoms in children exposed to a disaster depends on the degree of exposure (e.g., Lonigan et al, 1991 ; Korol et al, 2002 ). In the context of COVID-19, studies have also found that being infected oneself or having a relative who has been infected with or has died from COVID-19 are relevant risk factors for children’s mental health (e.g., Dönmez and Uçur, 2021 ; Luijten et al, 2021 ). Additionally, several qualitative and mixed-methods studies investigated COVID-19-related worries in children and adolescents during the early stages of the pandemic, when the lockdown was most severe.…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence of the depressive symptoms among children is studied several countries during Covid‐19 pandemic. The results differ in different regions, but approximately from 20% to 30% of children and adolescent aged 6–17 suffered depressive symptoms [52, 53]. The prevalence of the depressive symptoms among children has increased during pandemic situation [54].…”
Section: Discussionmentioning
confidence: 99%
“…The delayed onset of psychopathology induced by early-life trauma has presented the challenge of identifying the early-life roots of later-life psychiatric disorders. However, more recently, an emphasis on the subtle age-specific expression of later-life psychiatric disorders suggests there are earlier symptoms of dysfunction that serve as markers of later-life pathology (Shear et al, 2006;Bittner et al, 2007;Pine, 2007;Zeanah et al, 2016;Bushnell et al, 2020;Creswell et al, 2020;Gold et al, 2020;Ciuhan and Iliescu, 2021;Cuijpers et al, 2021;Donmez and Ucur, 2021;Havens et al, 2021;Smith and Pollak, 2021). For example, one reliable early-life marker of later-life pathology is observable through the increased expression of fear and anxiety, which is sometimes diagnosed as an anxiety disorder (Jovanovic et al, 2014;Grossmann and Jessen, 2017;Creswell et al, 2020).…”
Section: Infant Trauma Within a Social Context (Attachment) And Emerg...mentioning
confidence: 99%